KUSHON PODSHOLIGI DAVRIDA DINIY BAG‘RIKENGLIK ASOSLARINING TARIXIY JARAYONLARDA AKS ETISHI - Mamatov Azizbek, Ismoilov Ramazonxon (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article focuses on the spread of the ideas of religious tolerance in the Kushan kingdom, the diversity of the kingdom, the rise of the ideas of tolerance to the level of state policy and the introduction of Buddhist in Centrel Asian cultural life, Buddhist settlements are mentioned.